Analisis Pengaruh Gaya Belajar Siswa, Motivasi Belajar dan Peran Orang Tua terhadap Prestasi Belajar Siswa Kelas X TKJ pada Mata Pelajaran Jaringan Dasar di SMKN 6 Malang - Zahra Safanah Atari; Retno Indah Rokhmawati; Faizatul Amalia (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
This research was carried out based on the current condition, namely the Covid-19 pandemic, so learning activities were conducted. Education is currently experiencing challenges as a result of the COVID-19 pandemic, therefore the government issued a policy so that learning is done from home using online methods to suppress the spread of the virus. During this pandemic there was a change in the learning environment that influenced rning styles, learning motivation, and the role of parents on student learning achievement at home. This study aims to determine how the influence of learning styles, learning motivation, and the role of parents on the learning achievement of class X TKJ students in Basic Networking subjects at SMKN 6 Malang. The approach used in this research is a quantitative approach with the type of inferential analysis research. The sample in this study were students of class X TKJ 1 with a total of 30 students. Data retrieval of learning styles, learning motivation, and the role of parents on student achievement using a questionnaire distribution media using google form. The results showed that learning styles, learning motivation, and the role of parents together did not affect on student achievement. It was stated that H0 was accepted. The significance value obtained is 0.595 > 0.05; 0.040 > 0.05; 0.000 > 0.05.